Managing pain - Mann, Eileen (BMJ Publishing Group Ltd., 2003)
Managing pain effectively is one of the biggest challenges in medicine, and one of the areas of clinical practice where a good doctor-patient relationship can, potentially, help improve the end result. But it takes time to get this right—and requires help from other healthcare professionals, argues a nurse consultant in pain management